Eat Green, Get Lean: Promoting Sustainability Reduces Consumption. (September 2017) - Farmer, Adam; Breazeale, Michael; Stevens, Jennifer L.; Waites, Stacie F.
Food overconsumption contributes greatly to health problems that affect a large portion of the population while also straining the earth's natural resources. Attempts by policy makers to encourage sustainable food practices often focus more on the role of producers and less on the role of consumers, even though a growing number of consumers are concerned about the sustainability of their food products. Yet consumers often fail to perceive any immediate, personal benefits from consuming sustainably; instead, they envision future societal-level benefits. Three studies capturing actual behavior—the consumption of food and beverages—provide evidence that food promoted as sustainable can produce individual consumer benefits through reduced consumption. Study 1 shows the effect of sustainability in lessening consumption. Study 2 demonstrates how sustainability semantically primes a prosocial focus, which is the mechanism involved in the reduction of consumption. Study 3 then shows that this effect is enhanced for people with higher levels of self-control.